(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Traumatic spinal cord injury (TSCI) often leads to severe neurological impairment. Surgical decompression is a widely used intervention, but the extent and timeline of neurological recovery—particularly ASIA grade conversion—remain insufficiently documented in developing countries. Objective To evaluate ASIA grade improvement following surgical management in patients with incomplete TSCI. Methods This quasi-experimental study enrolled 38 patients with incomplete TSCI, who underwent surgical decompression across four tertiary hospitals in Dhaka, Bangladesh. ASIA impairment scale grades were recorded at admission and at 1, 3, and 6 months postoperatively. Statistical analysis included the Friedman test and chi-square tests to assess grade transitions. All statistical analysis were done by SPSS version 26.0 Results The mean age was 37.5 years, with male predominance (86.8%). Fall from height (63.2%) was the most common mechanism of injury, and L1 was the most frequently affected level (63.3%). At admission, most patients were ASIA D (60.5%). At 6 months, 81.6% improved to ASIA E. Overall, 97.4% experienced at least one-grade improvement, with conversion rates of 83.3% for ASIA B, and 100% for ASIA C and D. The Friedman test indicated a statistically significant improvement across time points (p = 0.001). Conclusion Surgical decompression in patients with incomplete TSCI is associated with substantial neurological recovery. ASIA grade conversion can serve as a reliable marker for monitoring surgical outcomes in such patients. BJMS, Vol. 25 No. 01 January’26 Page : 112-117